A Comprehensive and Advanced Mouse Model of Post‐Traumatic Epilepsy with Robust Spontaneous Recurrent Seizures. Issue 6 (7th June 2022) - Reddy, Doodipala Samba; Golub, Victoria M.; Ramakrishnan, Sreevidhya; Abeygunaratne, Hasara; Dowell, Samantha; Wu, Xin
Abstract: Traumatic brain injury (TBI) is a leading cause of epilepsy in military persons and civilians. Spontaneous recurrent seizures (SRSs) occur in the months or years following the injury, which is commonly referred to as post‐traumatic epilepsy (PTE). Currently, there is no effective treatment or cure for PTE; therefore, there is a critical need to develop animal models to help further understand and assess mechanisms and interventions related to TBI‐induced epilepsy. Despite many attempts to induce PTE in animals, success has been limited due to a lack of consistent SRSs after TBI. We present a comprehensive protocol to induce PTE after contusion brain injury in mice, which exhibit robust SRSs along with neurodegeneration and neuroinflammation. This article provides a complete set of protocols for injury, outcomes, troubleshooting, and data analysis. Our broad profiling of a TBI mouse reveals features of progressive, long‐lasting epileptic activity, hippocampal sclerosis, and comorbid mood and memory deficits. Overall, the PTE mouse shows striking consistency in recapitulating major hallmark features of human PTE. This mouse model will be helpful in assessing mechanisms of and interventions for TBI‐induced epileptogenesis, epilepsy, and neuropsychiatric dysfunction. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Inducing controlled cortical impact injuries Support Protocol : Creating the custom domed camp Basic Protocol 2 : Recording long‐term video‐EEG signals Basic Protocol 3 : Analyzing video‐EEG recordings